Original paperEvaluation of surgical treatment of rhinophyma with tangential shear of the lesion - Witmanowski, Henryk; Lewandowicz, Edward; Sobieszek, Daria; Łuczkowska, Magdalena; Rykała, Jan (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2012)
Introduction : Tuberosity of the nose is a slow, progressive, gentle process, leading to distortion and dysfunction of the nose. Underlying the change is perifollicular hypertrophy of the sebaceous glands, fibrous tissue proliferation and vascular changes of telangiectasia type. It is believed that it is the final stage of rosacea. Aim : To evaluate the effectiveness of surgical treatment using the method of tangential shear, based on a medical examination and subjective assessment of the effects of treatment by the patient. Material and methods: In the years 1998 to 2008 nine patients with moderate degree of rhinophyma were treated surgically by tangential shear, followed by electrocoagulation. The results were assessed according to a 4-point scale as very good, good, fair and poor. We evaluated the presence of postoperative complications (bleeding, infection, or other), healing time, the shape of the nose (size and symmetry), improved patency, reduction in the number of inflammatory conditions, widening of the field of view and long-term effects of treatment: disfiguring scars, uneven surface of the nose, nasal deformity and recurrence. Results : Among the 9 patients studied in 2 cases a very good result was achieved, in 5 good and in 2 satisfactory; no poor result was observed. Healing took an average of 6 weeks (1-15 weeks). None of the patients had postoperative complications. Seven patients were satisfied with both the size and symmetry of the nose, one unsatisfied with the size and 1 dissatisfied with the symmetry. Following the operation, 1 patient had disfiguring scars, 3 uneven surface of the nose, nasal deformity was observed in 2 cases and there was 1 recurrence. Of the 2 patients with a satisfactory result, 1 has been re-operated on, while the other was set an additional term of treatment. Conclusions : Surgical treatment of nasal tuberosity by tangential shear followed by electrocoagulation is effective, and burdened by low rates of complications. To achieve a good aesthetic and functional effect, a very experienced operator is recommended.